(untitled) (Journal of the College of Basic Education, 2022)
The quality of drinking water supplied to households plays an important role in public health. The length and quality of the water distribution networks play an important role in the quality of water. The studies that highlight the quality of drinking water supplied to the most densely populated in Baghdad (Al-Sadr City), as well as the relationship between the length of the drinking water distribution network and the quality of water are scanty in literature. The current study cove this gap. In the current study 170, tap water samples from 17 different areas of Sadr City, Baghdad, Iraq which is at different distances from the drinking water distribution station were collected. The pH, Total hardness, and concentrations of Chloride, Nitrite, Nitrate, Sulfite, Sulfate, Calcium, Magnesium, Iron, Lead, and Phosphate were measured. Proving bacterial contamination by conducting bacteriological tests (coliforms) was studied also. The results showed that five isolates of non-fecal coliform were isolated from samples collected from the areas furthest from the distribution station. The results showed that the specifications of the drinking water taken were within the standard specifications. The results also clearly showed the effect of the length of the distribution network on the water quality. Negative relationship (P<0.05) between the distance of distribution station (DDS) of water and pH values, total hardness, concentrations of chloride, and phosphate. The results also showed a positive relationship between DDS and concentrations of nitrites and sulfites, magnesium, and iron. There was no relationship between DDS and concentrations of nitrates, sulfates, and lead. It can be concluded from the current study that the length of the water distribution network has a major role in changing the specifications and quality of drinking water distributed to Al-Sadr City houses.